2017
DOI: 10.1200/jco.2017.35.15_suppl.5002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II cross-over study of abiraterone + prednisone (ABI) vs enzalutamide (ENZ) for patients (pts) with metastatic, castration-resistant prostate cancer (mCRPC).

Abstract: 5002 Background: ABI and ENZ are indicated as 1st line therapy for mCRPC but have not been directly compared. Optimal sequencing of these agents has not been prospectively evaluated and predictive biomarkers are lacking. Methods: Multicenter, phase 2 study randomizing treatment-naïve mCRPC pts to ABI vs ENZ, with cross over at PSA progression. Primary endpoints: response and time to PSA progression (TTPP, PCWG3 criteria) after 2nd line therapy. Reported here are secondary endpoints: PSA ≥50% decline (PSA50) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
0
27
0
6
Order By: Relevance
“…We need to see the exact rationale behind using docetaxel, abiraterone, or enzalutamide. Although Chi et al conducted a Phase II crossover study of abiraterone vs enzalutamide for patients with metastatic CRPC, it is still uncertain as to which agent might be optimal for first‐line treatment. Thus, today, there is no apparent rationale about the indication criteria and we did not have enough patients to clarify this in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We need to see the exact rationale behind using docetaxel, abiraterone, or enzalutamide. Although Chi et al conducted a Phase II crossover study of abiraterone vs enzalutamide for patients with metastatic CRPC, it is still uncertain as to which agent might be optimal for first‐line treatment. Thus, today, there is no apparent rationale about the indication criteria and we did not have enough patients to clarify this in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer cell lines, both docetaxel, and cabazitaxel were shown to interfere with the androgen receptor signaling by sharing a common cellular effect. Moreover, although more patients received abiraterone than enzalutamide in the mCRPC setting, existing retrospective and prospective data suggests no difference in rPFS according to the type of sHT used …”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer cell lines, both docetaxel, and cabazitaxel were shown to interfere with the androgen receptor signaling by sharing a common cellular effect. Moreover, although more patients received abiraterone than enzalutamide in the mCRPC setting, existing retrospective and prospective data suggests no difference in rPFS according to the type of sHT used 27,28. Whether the difference in time to radiographic progression observed in favor of sHT were influenced by the small sample size of the two groups and the timing of restaging scans could not be determined.…”
mentioning
confidence: 97%
“…6 A total of 200 patients with treatment-naïve mCRPC were randomized to AAP (at a dose of 1000/10 mg daily) or enzalutamide (160 mg daily) and were crossed over to the other therapy at progression. The primary objective was to compare response and time to PSA progression (TTPP) after…”
mentioning
confidence: 99%
“…6 A total of 200 patients with treatment-naïve mCRPC were randomized to AAP (at a dose of 1000/10 mg daily) or enzalutamide (160 mg daily) and were crossed over to the other therapy at progression. The primary objective was to compare response and time to PSA progression (TTPP) after Results showed that, although the enzalutamide arm demonstrated a more substantial PSA response at 12 weeks (77% compared to 55%), there were no significant differences between arms with respect to TTPP in the first-line setting (AAP 7.4 months vs. enzalutamide 8.0 months; HR 0.88; 95% CI 0.61-1.27).…”
mentioning
confidence: 99%